Characterization of DNA methylation reader proteins in Arabidopsis thaliana - Cahn, Jonathan; Lloyd, James P.B.; Karemaker, Ino D.; Jansen, Pascal W.T.C.; Pflueger, Jahnvi; Duncan, Owen; Petereit, Jakob; Bogdanovic, Ozren; Millar, A. Harvey; Vermeulen, Michiel; Lister, Ryan (Genome Research, 2024)
In plants, cytosine DNA methylation (mC) is largely associated with transcriptional repression of transposable elements, but it can also be found in the body of expressed genes, referred to as gene body methylation (gbM). gbM is correlated with ubiquitously expressed genes; however, its function, or absence thereof, is highly debated. The different outputs that mC can have raise questions as to how it is interpreted—or read—differently in these sequence and genomic contexts. To screen for potential mC-binding proteins, we performed an unbiased DNA affinity pull-down assay combined with quantitative mass spectrometry using methylated DNA probes for each DNA sequence context. All mC readers known to date preferentially bind to the methylated probes, along with a range of new mC-binding protein candidates. Functional characterization of these mC readers, focused on the MBD and SUVH families, was undertaken by ChIP-seq mapping of genome-wide binding sites, their protein interactors, and the impact of high-order mutations on transcriptomic and epigenomic profiles. Together, these results highlight specific context preferences for these proteins, and in particular the ability of MBD2 to bind predominantly to gbM. This comprehensive analysis of Arabidopsis mC readers emphasizes the complexity and interconnectivity between DNA methylation and chromatin remodeling processes in plants.
10.1101/gr.279379.124